Plasminogen fragments K 1-3 and K 5 bind to different sites in fibrin fragment DD - T. V. Grinenko; L. G. Kapustianenko; T. A. Yatsenko; O. I. Yusova; V. N. Rybachuk (The Ukrainian Biochemical Journal, 2016)
Specific plasminogen-binding sites of fibrin molecule are located in Аα148-160 regions of C-terminal domains. Plasminogen interaction with these sites initiates the activation process of proenzyme and subsequent fibrin lysis. In this study we investigated the binding of plasminogen fragments K 1-3 and K 5 with fibrin fragment DD and their effect on Glu-plasminogen interaction with DD. It was shown that the level of Glu-plasminogen binding to fibrin fragment DD is decreased by 50-60% in the presence of K 1-3 and K 5. Fragments K 1-3 and K 5 have high affinity to fibrin fragment DD (Kd is 0.02 for K 1-3 and 0.054 μМ for K 5). K 5 interaction is independent and K 1-3 is partly dependent on C-terminal lysine residues. K 1-3 interacts with complex of fragment DD-immobilized K 5 as well as K 5 with complex of fragment DD-immobilized K 1-3. The plasminogen fragments do not displace each other from binding sites located in fibrin fragment DD, but can compete for the interaction. The results indicate that fibrin fragment DD contains different binding sites for plasminogen kringle fragments K 1-3 and K 5, which can be located close to each other. The role of amino acid residues of fibrin molecule Аα148-160 region in interaction with fragments K 1-3 and K 5 is discussed.